Fungal diversity notes 253–366: taxonomic and phylogenetic contributions to fungal taxa - Guo Jie Li (2018)
© 2016, School of Science. Notes on 113 fungal taxa are compiled in this paper, including 11 new genera, 89 new species, one new subspecies, three new combinations and seven reference specimens. A wide geographic and taxonomic range of fungal taxa are detailed. In the Ascomycota the new genera Angustospora (Testudinaceae), Camporesia (Xylariaceae), Clematidis, Crassiparies (Pleosporales genera incertae sedis), Farasanispora, Longiostiolum (Pleosporales genera incertae sedis), Multilocularia (Parabambusicolaceae), Neophaeocryptopus (Dothideaceae), Parameliola (Pleosporales genera incertae sedis), and Towyspora (Lentitheciaceae) are introduced. Newly introduced species are Angustospora nilensis, Aniptodera aquibella, Annulohypoxylon albidiscum, Astrocystis thailandica, Camporesia sambuci, Clematidis italica, Colletotrichum menispermi, C. quinquefoliae, Comoclathris pimpinellae, Crassiparies quadrisporus, Cytospora salicicola, Diatrype thailandica, Dothiorella rhamni, Durotheca macrostroma, Farasanispora avicenniae, Halorosellinia rhizophorae, Humicola koreana, Hypoxylon lilloi, Kirschsteiniothelia tectonae, Lindgomyces okinawaensis, Longiostiolum tectonae, Lophiostoma pseudoarmatisporum, Moelleriella phukhiaoensis, M. pongdueatensis, Mucoharknessia anthoxanthi, Multilocularia bambusae, Multiseptospora thysanolaenae, Neophaeocryptopus cytisi, Ocellularia arachchigei, O. ratnapurensis, Ochronectria thailandica, Ophiocordyceps karstii, Parameliola acaciae, P. dimocarpi, Parastagonospora cumpignensis, Pseudodidymosphaeria phlei, Polyplosphaeria thailandica, Pseudolachnella brevifusiformis, Psiloglonium macrosporum, Rhabdodiscus albodenticulatus, Rosellinia chiangmaiensis, Saccothecium rubi, Seimatosporium pseudocornii, S. pseudorosae, Sigarispora ononidis and Towyspora aestuari. New combinations are provided for Eutiarosporella dactylidis (sexual morph described and illustrated) and Pseudocamarosporium pini. Descriptions, illustrations and / or reference specimens are designated for Aposphaeria corallinolutea, Cryptovalsa ampelina, Dothiorella vidmadera, Ophiocordyceps formosana, Petrakia echinata, Phragmoporthe conformis and Pseudocamarosporium pini. The new species of Basidiomycota are Agaricus coccyginus, A. luteofibrillosus, Amanita atrobrunnea, A. digitosa, A. gleocystidiosa, A. pyriformis, A. strobilipes, Bondarzewia tibetica, Cortinarius albosericeus, C. badioflavidus, C. dentigratus, C. duboisensis, C. fragrantissimus, C. roseobasilis, C. vinaceobrunneus, C. vinaceogrisescens, C. wahkiacus, Cyanoboletus hymenoglutinosus, Fomitiporia atlantica, F. subtilissima, Ganoderma wuzhishanensis, Inonotus shoreicola, Lactifluus armeniacus, L. ramipilosus, Leccinum indoaurantiacum, Musumecia alpina, M. sardoa, Russula amethystina subp. tengii and R. wangii are introduced. Descriptions, illustrations, notes and / or reference specimens are designated for Clarkeinda trachodes, Dentocorticium ussuricum, Galzinia longibasidia, Lentinus stuppeus and Leptocorticium tenellum. The other new genera, species new combinations are Anaeromyces robustus, Neocallimastix californiae and Piromyces finnis from Neocallimastigomycota, Phytophthora estuarina, P. rhizophorae, Salispina, S. intermedia, S. lobata and S. spinosa from Oomycota, and Absidia stercoraria, Gongronella orasabula, Mortierella calciphila, Mucor caatinguensis, M. koreanus, M. merdicola and Rhizopus koreanus in Zygomycota.